Corneal Cross-Linking Window Absorption (CXL-WA) as an Adjuvant Therapy in the Management of Aspergillus niger Keratitis - Pietro Rosetta; Emanuela F. Legrottaglie; Luca Pagano; Paolo Vinciguerra (Case Reports in Ophthalmological Medicine)
Purpose. To evaluate the effectiveness of corneal cross-linking window absorption (CXL-WA) as an adjuvant therapy for Aspergillus keratitis. Methods. A 90-year-old male came to our clinic complaining of hyperemic conjunctivitis and progressive visual loss in the right eye. Slit-lamp examination showed keratic precipitates, severe corneal opacity, and stromal edema. Corneal scraping culture was positive for Aspergillus niger. Because the clinical condition did not sufficiently improve with antifungal therapy, the patient underwent CXL-WA as an adjuvant therapy. Results. During the first week after treatment, the Tyndall effect, corneal edema, and signs of ocular inflammation progressively lessened. At the third postoperative month, the cornea was stable without signs of fungal keratitis. However, after this period, a descemetocele appeared in the cornea (2 × 2 mm in diameter), so the patient underwent a corneal penetrating keratoplasty. Histological evaluation of the removed corneal tissue revealed the presence of hyphae and fungal infection. Conclusions. We reported a case of in vivo CXL-WA used as an adjuvant therapy for deep stromal Aspergillus keratitis. CXL did not completely eradicate the fungal infection which caused perforation 4 months after treatment and it still cannot be considered a definitive solution to mycotic keratitis, which maintains a poor long-term prognosis.